2010
DOI: 10.1007/s00281-010-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

When autophagy meets viruses: a double-edged sword with functions in defense and offense

Abstract: Autophagy is a ubiquitous catabolic process that ensures organism’s well-being by sequestering a wide array of undesired intracellular constituents into double-membrane vesicles termed autophagosomes for lysosomal degradation. Interest in autophagy research has recently gained momentum as it is increasingly being recognized to play fundamental roles in diverse aspects of human pathophysiology including virus infection and its subsequent complications. This review discusses recent advances in autophagy studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 99 publications
1
71
0
Order By: Relevance
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a highly conserved process that generates doublemembrane vesicles that engulf and sequester portions of the cytoplasm to be delivered to the lysosome for degradation (6,7). Autophagy is induced in response to diverse stress stimuli, including nutrient starvation, endoplasmic reticulum (ER) stress, oxidative stress, pathogen-associated molecular patterns (PAMPs), and virus infection (6).…”
mentioning
confidence: 99%
“…One possibility is that cytoplasmic HMGB1 is involved in the induction of autophagy in HCVinfected cells. Autophagy is known to play an important role in host immunity against virus infections (23). On the other hand, autophagy is known to be required for HCV replication (12), and the knockdown of proteins involved in autophagy enhances the innate immune response in HCV-infected hepatocytes (21,32).…”
Section: Discussionmentioning
confidence: 99%